2020
DOI: 10.3389/fonc.2020.00745
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Osteosarcoma—Pilot Study on the Expression of Osteobiologic Characteristics and Hypothesis on Metastasis

Abstract: Background: Craniofacial osteosarcomas (COS) and extracranial osteosarcomas (EOS) show distinct clinical differences. COS show a remarkably lower incidence of metastases and a better survival. However, in contrast to EOS, they show a poor response to neoadjuvant chemotherapy. Tumor-associated macrophages and their polarization as well as developmental biological signaling pathways are possible candidates for explaining the clinical differences between COS and EOS. The aim of the study was to analyze differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…It was reported that M1 macrophages promoted inflammatory responses, were capable of antigen presentation and the activation of T cells, and therefore have anti-tumor and anti-metastatic effects (81,82). Manuel Weber et al compared the difference in macrophage infiltration between craniofacial osteosarcoma (COS) and extracranial osteosarcoma (EOS) and found that M1 macrophages were more infiltrated in COS, which could explain the low probability of metastasis in COS (83). M2 macrophages were reported to have immunomodulatory effects and were associated with wound healing, immunosuppression, tumor progression and metastasis (84)(85)(86).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that M1 macrophages promoted inflammatory responses, were capable of antigen presentation and the activation of T cells, and therefore have anti-tumor and anti-metastatic effects (81,82). Manuel Weber et al compared the difference in macrophage infiltration between craniofacial osteosarcoma (COS) and extracranial osteosarcoma (EOS) and found that M1 macrophages were more infiltrated in COS, which could explain the low probability of metastasis in COS (83). M2 macrophages were reported to have immunomodulatory effects and were associated with wound healing, immunosuppression, tumor progression and metastasis (84)(85)(86).…”
Section: Discussionmentioning
confidence: 99%
“…Manuel Weber et al. compared the difference in macrophage infiltration between craniofacial osteosarcoma (COS) and extracranial osteosarcoma (EOS) and found that M1 macrophages were more infiltrated in COS, which could explain the low probability of metastasis in COS ( 83 ). M2 macrophages were reported to have immunomodulatory effects and were associated with wound healing, immunosuppression, tumor progression and metastasis ( 84 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different clinical behavior of craniofacial versus extracranial osteosarcoma may be due to the different developmental biology of craniofacial and extracranial bone. A different activation of the Hedgehog signaling pathway and also possible immunologic differences between craniofacial and extracranial osteosarcomas have already been shown [ 19 ].…”
Section: Clinical Impact Of the Craniofacial Developmentmentioning
confidence: 99%
“…In adolescence, the disease often occurs in the long bone metaphysis of the extremities, such as the distal femur and the proximal tibia [ 4 , 5 ]. For the elderly, however, the predilection sites are diverse, which can also occur in the craniofacial region [ 6 ]. OSA has a high propensity to metastasize, specifically to the lungs, with more than 85% of patients developing lung metastasis at the time of initial treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%